An All Too Real Neverending Story: Federal Income Tax Complexity - Rosacker, Robert E.; Rosacker, Kirsten M. (Journal of Applied Business and Economics, 2023)
This research effort extends the work of Rosacker and Davies (1997) to re-validate their tax complexity model. The empirical outcomes of the current study permit a comparative assessment of tax complexity across time while additionally allowing for the immediate consideration of several significant tax reforms enacted within the Tax Cuts and Jobs Act of 2017. The primary research question is whether the model helps inform tax policy choices targeted at decreasing tax complexity through a focus on the enacted tax reforms, a critical objective specified for the original research effort. This study enhances the literature by assessing and comparing federal income tax complexity under prior, existing, and subsequent tax systems. A complexity measurement model has been created utilizing data developed under the IRS, allowing the investigation of a database created annually by the IRS.